Respuesta :
Answer:
x= 2/7
Step-by-step explanation:
Multiply both sides by the common denominator
3x^2 +6x−2=3x^2 −x
Move everything to the left side.
3x^2+6x-2-3x^2+x=0
Simply.
7x-2=0
Separate the cosntants and variables.
7x=0+2
Add or subtract zero
7x=2
Then divide both sides by 7.
7x/7=2/7
Cancel out common factors in the numerator and denominator
x=2/7
Answer:
x = 2/7
Step-by-step explanation:
You want to solve the equation 3x/(3x-1) + 2/x = 1.
Solution
It works nicely to subtract 1 from both sides, then simplify.
[tex]\dfrac{3x}{3x-1}+\dfrac{2}{x}=1\\\\\dfrac{3x}{3x-1}\cdot\dfrac{x}{x}+\dfrac{2}{x}\cdot\dfrac{3x-1}{3x-1}-\dfrac{x(3x-1)}{x(3x-1)}=0\\\\\dfrac{3x^2+6x-2-3x^2+x}{x(3x-1)}=0\qquad\text{combine terms}\\\\\dfrac{7x-2}{x(3x-1)}=0\qquad\text{simplify}\\\\7x-2=0\qquad\text{expression is 0 when numerator is 0}\\\\\boxed{x=\dfrac{2}{7}}\qquad\text{add 2, divide by 7}[/tex]
__
Additional comment
The values x=0 and x=1/3 would make the denominator zero, so are excluded from the domain of the equation. By working the problem this way, we ensure that extraneous solutions do not present themselves.